THE HOLY QURAN PERSPECTIVE OF BUSINESS COMPETITION - Arini - Pratiwi; Hasyim Aidid; Misbahuddin Misbahuddin (IAIN Bone, 2022)
This research aims to find out the term, the definition of business competition from the Qur'an perspective and to know the concept of business competition from the Qur'an perspective so that it can be a contribution to the treasures of Islamic economic science development and increasingly believe that the Qur'an can be a form of guidance in implementing healthy business competition for the realization of the primary purpose of Islamic law, namely the benefit of the ummah. The types of research used in this research are library research and doctrinal research by using descriptive analysis to describe the focus of the problem to be discussed objectively. The analysis method is used to obtain and find out the study of business competition from the Perspective of the Qur'an. The approach used is the theological, religious approach and conceptual approach. The conceptual approach is used concerning views and doctrines in Islamic law. The results of the study found that the terms of business competition in the Qur'an are not found in the Qur'an but can use the words سبق and استبق to refer to competition. While the terms of competition are found in QS. Al Baqarah (2):148, QS. Al Maidah (5):48, QS. Al Mu'minun (23):61. There are two concepts of competition for the Qur'anic perspective, first based on QS. Al Baqarah (2): 148, QS. Al Maidah (5): 48, QS. Al Mu'minun (23): 61 shows the conclusion that competing/competing is an attempt to compete positively (فَاسْتَبِقُوا الْخَيْرَات) by contributing sufficiently and not getting rid of entrepreneurs / other business actors and telling entrepreneurs/business actors not to harm and endanger other businessmen/business actors; To realize healthy business competition and improve the welfare of the people, every business actor must compete to provide the best products/services for consumers regardless of whether the consumer has differences in religion, ethnicity, race, or culture with business actors. Second, the concept of business competition obliges all his people to seek sustenance from the expanse of God's gift in a halal way where the search for sustenance must be carried out based on the path of goodness for happiness and benefit of humanity. The basic principles that underlie the obligation to seek halal sustenance have been affirmed by Allah SWT in Q.S. al-Mulk: 15 and Q.S. Al Baqarah: 168.